2023
DOI: 10.1111/jan.15607
|View full text |Cite
|
Sign up to set email alerts
|

How does government policy influence the employment and training of nurse practitioners and physician assistants? A realist analysis using qualitative interviews

Abstract: Aims:The aim of this study was to develop insights into how and why Dutch government policies on deployment and training of nurse practitioners and physician assistants have effect and under what circumstances.Design: A realist analysis using qualitative interviews. Methods: Data analysis of 50 semi-structured interviews conducted in 2019 with healthcare providers, sectoral and professional associations, and training coordinators. Stratified purposive and snowball sampling were used. Results: Policies stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Upskilling refers to situations where nurses must perform the tasks of, e.g., physicians. A Dutch study about the introduction of nurse practitioners showed the great variety between the types of healthcare institutions that work with nurse practitioners [67]. The main explanation is the lack of knowledge in healthcare organizations about the possibilities to transfer tasks from physicians to nurses (nurse practitioners).…”
Section: Task Shifting: Up-and Down-skillingmentioning
confidence: 99%
“…Upskilling refers to situations where nurses must perform the tasks of, e.g., physicians. A Dutch study about the introduction of nurse practitioners showed the great variety between the types of healthcare institutions that work with nurse practitioners [67]. The main explanation is the lack of knowledge in healthcare organizations about the possibilities to transfer tasks from physicians to nurses (nurse practitioners).…”
Section: Task Shifting: Up-and Down-skillingmentioning
confidence: 99%